New pyridine and chromene scaffolds as potent vasorelaxant and anticancer agents. Issue 47 (2nd September 2021) - Dawood, Dina H.; Srour, Aladdin M.; Saleh, Dalia O.; Huff, Kelley J.; Greco, Francesca; Osborn, Helen M. I.
Abstract : Series of pyridine- (3a–o ) and/or chromene- (4a–e ) carbonitrile scaffolds have been designed, synthesized and evaluated for their bi-function activities, 3d was the only common derivative having combined vasodilation and anticancer properties. Abstract : Based on studies that have reported the association between cancer and cardiovascular diseases, new series of pyridine- (3a–o ) and/or chromene- (4a–e ) carbonitrile analogous were designed, synthesized and screened for their vasodilation and cytotoxic properties. The majority of the new chemical entities demonstrated significant vasodilation efficacies, compounds 3a, 3h, 3j, 3m, 3o, 4d and 4e exhibited the most promising potency with IC50 = 437.9, 481.0, 484.5, 444.8, 312.1, 427.6 and 417.2 μM, respectively, exceeding prazosin hydrochloride (IC50 = 487.3 μM). Compounds 3b–e, 3k and 3l also, revealed moderate vasodilation activity with IC50 values ranging from 489.7 to 584.5 μM. In addition, the anti-proliferative activity evaluation of the experimental compounds at 10 μM on the MCF-7 and MDA-MB 231 breast cancer cell lines illustrated the excellent anti-proliferative properties of derivatives 3d, 3g and 3i . Compound 3d was the most potent analogue with IC50 = 4.55 ± 0.88 and 9.87 ± 0.89 μM against MCF-7 and MDA-MB 231, respectively. Moreover, compound 3d stimulated apoptosis and cell cycle arrest at the S phase in MCF-7 cells in addition to its capability in accumulation of cells in pre-G1 phase and activating caspase-3. Furthermore, the molecular docking of 3d was performed to discover the binding modes within the active site of caspase-3. 3d, as the only common bi-functional agent among the tested hits, demonstrated that new pyridine-3-carbonitrile derivatives bearing cycloheptyl ring systems offer potential as new therapeutic candidates with combined vasodilation and anticancer properties.